Perceraian Sebab Kawin Paksa (Studi Kasus di Pengadilan Agama Jember) - Abdul Hamid (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2017)
In Islamic law and positive law that a marriage must be conducted in accordance with the rules and regulations. Both of these indicate that the carrying out of a marriage should be based on the terms and the pillars of Islam and the positive law. By law if the marriage ceremony has done, then the resulting rights and obligations between husband and wife. If the marriage between husband and wife or one of them does not want to perform its obligations, it shall do divorce. In the KHI mentioned that one of the causes of marriage breakdown is divorce and the reasons that can be used to litigate divorce one of them is between a husband and wife constantly disputes and quarrels and no hope of living in harmony again in the household. From this arises because a spouse is unwilling to perform its obligations due to any coercion in marriage.